Mobilizing COVID-19 Science. (November 2020) - Adams, Jimi; Light, Ryan; Theis, Nicholas
While there are many uncertainties about the ensuing COVID-19 pandemic, scientific mobilization that integrates knowledge from across the wide-ranging intersection of applicable expertise will optimize our response strategy. As we continue to coordinate these efforts, sociological contributions can continue to identify improved social coordination opportunities, even while practicing social distancing.